2013
DOI: 10.2215/cjn.04370512
|View full text |Cite
|
Sign up to set email alerts
|

Serum Adiponectin Levels and Mortality after Kidney Transplantation

Abstract: SummaryBackground and objectives Adiponectin (ADPN), an adipose tissue-derived hormone, has protective properties with respect to atherogenesis, inflammation, and energy homeostasis. Its beneficial role has not been consistent in patients with CKD or those undergoing dialysis.Design, setting, participants, & measurements This study examined the association of plasma ADPN levels in 987 prevalent kidney transplant recipients (mean age 6 SD, 51.0612.8 years; estimated GFR, 52.8621.9 ml/min per 1.73 m 2 ; median t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
17
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 20 publications
2
17
0
Order By: Relevance
“…Despite the direct association between serum adiponectin and CV mortality is difficult to reconcile with the well-recognized role of adiponectin as an anti inflammatory, anti-atherogenic and insulin sensitizer factor [2,3] and with the previously reported association with reduced risk of CHD [6,7,27], the same counter intuitive finding has been recently described in individuals from the general population and several selected clinical setting [1117,1923]. In addition, high adiponectin levels have been reported to predict all-cause mortality in the general population and in patients with CV disease [1821], as well as in elderly people with type 2 diabetes [44].…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Despite the direct association between serum adiponectin and CV mortality is difficult to reconcile with the well-recognized role of adiponectin as an anti inflammatory, anti-atherogenic and insulin sensitizer factor [2,3] and with the previously reported association with reduced risk of CHD [6,7,27], the same counter intuitive finding has been recently described in individuals from the general population and several selected clinical setting [1117,1923]. In addition, high adiponectin levels have been reported to predict all-cause mortality in the general population and in patients with CV disease [1821], as well as in elderly people with type 2 diabetes [44].…”
Section: Discussionmentioning
confidence: 84%
“…Thus, it is surprising that, high adiponectin levels predict increased risk of heart failure (HF) [9,10] as well as CV mortality in the general population and in selected clinical settings [1121]. A similar unexpected paradoxical association with the risk of CV mortality has been also described in patients with type 1 diabetes [22] and in kidney transplant recipients [23]. Whether this is the case also among patients with type 2 diabetes has never been addressed.…”
mentioning
confidence: 94%
“…To summarize, circulating levels of APN are high in patients with chronic kidney failure, particularly in end-stage renal disease. Elevated levels of APN in this population are positively correlated with markers of systemic inflammation and associated with higher risk of death [89]. Although clearance of APN is mostly mediated by the liver [90], reduced renal excretion - rather than suppressed production by adipocytes - has been proposed as the mechanism for the elevated circulating levels of APN in chronic kidney disease [9, 88].…”
Section: Adiponectin In Human Inflammatory and Immune-mediated Dismentioning
confidence: 99%
“…Serum APN levels increase with progression of chronic graft-versus-host disease (GVHD) after allogeneic stem cell transplantation and decrease as GVHD improves, indicating a positive association between APN and GVHD severity [108]. In recipients of kidney transplants, low levels of APN predict allograft failure [109], although a different study demonstrates that elevated APN levels are not associated with protection from transplant failure [89]. As mentioned above, contradictory, possibly strain-dependent, results have also been reported for the role of APN in mouse models of heart and skin transplantation [55, 56, 72].…”
Section: Adiponectin In Human Inflammatory and Immune-mediated Dismentioning
confidence: 99%
“…In CKD various adipocytokines could play a role enhancing endothelial dysfunction, oxidative stress, inflammation, atherosclerosis, kidney sympathetic activity, blood pressure, and anaemia [24,25]. Alam et al revealed that elevated adiponectin concentration is linked to higher risk for death in adult CKD patients after kidney transplantation [26]. However, they did not document the higher rate of allograft failure in these patients.…”
Section: Discussionmentioning
confidence: 99%